Particulate emissions from the co-combustion of forest biomass and sewage sludge in a bubbling fluidised bed reactor - Calvo, A. I. (2018)
In the present study, particulate emissions from the co-combustion of forest biomass residues with sewage sludge in a pilot-scale bubbling fluidised bed combustor were characterised. The combustion flue gas was exhausted to the atmosphere after passing through a cyclone separator. Physical-chemical characteristics of the particles were studied: i) morphology and aerosol size, surface and volume distributions before the cyclone and ii) chemical composition (carbonates, water soluble-inorganic ions, organic and elemental carbon) before and after the cyclone. Chemical composition data were used to calculate aerosol density and refractive index. Aerosols showed a unimodal size distribution with a geometric mean diameter of 2.25 ± 0.02 μm and a geometric standard deviation of 1.27 ± 0.01. The surface and volume mean diameters were 2.64 ± 0.02 μm and 2.91 ± 0.05 μm, respectively. Water-soluble inorganic ions were predominant in the fine particle fraction (PM2.5). The filters were loaded of crystallised mineral particles. The analysis revealed a dominance of calcium carbonate/oxide and halide (NaCl or KCl), sulphate and aluminosilicate nanocrystals forming larger mixed aggregates.